A designed cell-penetrating human SOCS2 protein suppresses GH-dependent cancer cell proliferation. Issue 2 (1st February 2019) - Miyamoto, Azusa; Masuhiro, Yoshikazu; Seki, Taiichiro; Hanazawa, Shigemasa; Shiba, Hajime
ABSTRACT: Suppressor of cytokine signaling (SOCS) 2, a negative regulator of growth hormone (GH) and insulin-like growth factor 1 (IGF-1), which is associated with acromegaly and cancers, is a promising candidate molecule for treating various diseases. To facilitate its use in protein therapy, we designed and constructed a human SOCS2 protein containing a membrane-permeable peptide sequence and expressed it in an Escherichia coli system. The partially purified recombinant protein was effectively delivered into several cancer cell lines and inhibited cell growth. Biochemical analysis showed that the recombinant SOCS2 protein interacted with growth hormone receptor (GHR) and downregulated GH-STAT5 signaling target genes. Our results suggest that the designed cell-penetrating SOCS2 protein will be useful in intercellular protein therapy to cure cancers. Abbreviations: SOCS: suppressor of cytokine signaling; GH: growth hormone; GHR: growth hormone receptor; IGF-1: insulin-like growth factor 1; CP: cell-penetrating; STAT: signal transducer and activator of transcription; JAK: Janus kinase; HNF: hepatocyte nuclear factor; MTM: membrane-translocating motif; HIV: human immunodeficiency virus Graphical abstract: : Our produced cell-membrane penetrating human SOCS2 proteins were effectively delivered into several cell lines and inhibited cell growth by suppressing the JAK-STAT5 signal.